Hungary : 2021 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Hungary's economy entered the COVID-19 pandemic on a strong footing and the authorities responded swiftly and strongly to the crisis it triggered. While the lockdowns weighed heavily on activity, the fast vaccination pace is allowing an early relaxation of containment measures, and the economy has started to rebound.